A Conceptual Framework to Support Organizational Knowledge Transfer Evaluation - Ferreira, Williby; Saraiva, Juliana; Soares, Sérgio (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Evaluating Knowledge Transfer (KT) is critical for driving organizational learning, optimizing operational efficiency, and fostering innovation. However, knowledge on this topic remains unsystematized, existing solutions lack empirical validation, and standardized approaches are not widely adopted. This paper proposes an approach to support KT evaluation. To this end, a rapid review was conducted, and the Design Science Research Methodology was employed to model the approach. Given the impact of KT on organizational information flows and decision support systems, we present an overview of the systematization of knowledge on KT evaluation and the structure of its key processes and elements.